Interactional Strategies Used by Low Level Learners in Public Speaking Class: Strategi Interaksi yang Digunakan oleh Pembelajar Tingkat Rendah di Kelas Public Speaking - Astutik, Yuli (JEES (Journal of English Educators Society), 2017)
This research article described the interactional strategies used by low learners in public speaking class. A qualitative study on whether or not low learners used the aspects of interactional strategies was the main focus. This paper also aimed to know what aspects mostly used and the factors that cause this problem. Observing and interviewing to six subjects regarding on the use of interactional strategies: exemplification, confirmation checks, comprehension checks, repetition, clarification requests, repetition requests, exemplification requests, and assistance appeal were carried out. Finding indicated that from six low learners, only two who did not apply interactional strategies in all situations. Four students have applied 3 – 4 interactional strategies in the case they were as the speaker. In another side, when they were the listeners, they did not apply the interactional strategies. The result showed that repetition was the interactional strategy mostly used by low learners. Nevertheless, the reason of using it was not proper reason. The further finding indicated some factors cause low learners did not use four interactional strategies such as fluency, grammar, lack of vocabulary and pronunciation in addition to the English practice merely in the formal situation.